Pengaplikasian Model Pembelajaran Project Based Learning (PjBL) Berbasis Karakteristik Serangga di Sekitar Danau Ranu Kumbolo pada Mata Kuliah Entomologi - Ngulandoro, Harry; Prawira, Jamaluddin; Purnatapa, Makmur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The online learning policy was implemented during the Covid 19 pandemic in various countries in the world. Problems arise in learning biology that requires laboratory experiment activities. This research provides an innovation in entomology learning with the Project Based Learning (PjBL) learning model using insect biodiversity in the local ecosystem, namely Lake Ranu Kumbolo. This study aims to determine the ability of science process skills and student responses using the Project Based Learning (PjBL) learning model. Project Based Learning (PjBL) is one of the learning models that are set in the independent learning process to learn independent campuses. The research was conducted with exploratory descriptive research method. Science process skills and student project products are measured using a rubric. Student learning outcomes are measured using quiz questions with the google form application. Meanwhile, student responses were measured using a questionnaire. Based on the results of the study, it showed that the science process skills of students who were taught using the Project Based Learning (PjBL) learning model were in the good and very good categories. The output produced is a practicum guide based on the assessment rubric which is in good and very good grades. Student responses about the application of the Project Based Learning (PjBL) learning model in entomology courses are in the agree and strongly agree categories. Student learning outcomes showed an average in the good and very good categories. The application of the Project Based Learning (PjBL) learning model is able to stimulate the ability of science processes and student learning outcomes in entomology courses. The Project Based Learning (PjBL) learning model is very appropriate to be applied to fields of science that require a lot of experimental activities. Because it is carried out in small research groups, the Project Based Learning (PjBL) learning model is very appropriate to be applied in learning during the Covid 19 pandemic.